Pengaruh Lingkungan Kerja Dan Motivasi Kerja Terhadap Kinerja Pegawai Di Kantor Dinas Perindustrian, Perdagangan, Koperasi, Dan Ukm Kabupaten Toraja Utara - Renaldi Emba Sarungallo; Althon K. Pongtuluran; Adriana Madya Marampa (Journal Of Business, Finance, and Economics (JBFE), 2024)
This research aims to determine the influence of the work environment and work motivation on employee performance at the office of the Department of Industry, Trade, Cooperatives and Ukm, North Toraja Regency. The sampling technique in this research used the total sampling method where the entire population was sampled as 32 State Civil Servants, the data collection technique used a questionnaire. The data analysis technique used in this research is a quantitative method with the SPSS version 25 application, using multiple linear regression analysis, classical assumption test, t test, f test and coefficient of determination. The research results show that there is an influence of the independent variables work environment and work motivation on the dependent variable employee performance, this can be seen through the f test by obtaining a significance value for the influence of X1 and X2 on Y of 0.000. This significance value is smaller than 0.05, when compared with the calculated F value with F table, it is obtained 35.017 > 3.32, so it can be concluded that there is an influence of the work environment and work motivation on the performance of employees of the Department of Industry, Trade, Cooperatives and Ukm North Toraja district. The influence of the work environment and work motivation on employee performance is 70.7%.